1999
DOI: 10.2134/jeq1999.00472425002800050016x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite and the Two Stages of Nitrification in Nitrogen Polluted Onondaga Lake, New York

Abstract: Nitrite (NO−2) concentrations in the upper waters of N polluted Onondaga Lake, New York, are documented for the April through October interval for a 10‐yr (1989–1998) period. Inputs of NO−2 from a domestic waste treatment facility (METRO) and tributaries (4) to the lake are quantified for four of the years (1991–1994). The NO−2 concentrations measured in Onondaga Lake (e.g., annual maxima in the range 200–1000 mg N m 3) are some of the highest reported for lakes and rivers in the literature. These levels repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 0 publications
2
34
0
Order By: Relevance
“…8 Effect of NH þ 4 load on nitrite accumulation expressed as part of nitrite in the amount of total oxidized nitrogen ðTON ¼ NO À 2 þ NO À 3 Þ (after Joo et al 2000) Rev Environ Sci Biotechnol (2007 accumulates in an activated sludge plant especially over the summer period. Also Gelda et al (1999) found higher nitrite concentrations in a wastewater treatment facility without denitrification over the summer period (June to September). As follows from the formula describing the equilibrium of NH 3 =NH þ 4 and of HNO 2 =NO À 2 , temperature plays a role in the respective concentrations in the water phase.…”
Section: Temperaturementioning
confidence: 88%
See 1 more Smart Citation
“…8 Effect of NH þ 4 load on nitrite accumulation expressed as part of nitrite in the amount of total oxidized nitrogen ðTON ¼ NO À 2 þ NO À 3 Þ (after Joo et al 2000) Rev Environ Sci Biotechnol (2007 accumulates in an activated sludge plant especially over the summer period. Also Gelda et al (1999) found higher nitrite concentrations in a wastewater treatment facility without denitrification over the summer period (June to September). As follows from the formula describing the equilibrium of NH 3 =NH þ 4 and of HNO 2 =NO À 2 , temperature plays a role in the respective concentrations in the water phase.…”
Section: Temperaturementioning
confidence: 88%
“…In this way the nitrification is stopped at nitrite so that less oxygen is needed and subsequent denitrification demands less external carbon source (Jetten et al 1997;Hellinga et al 1998Hellinga et al , 1999. A modeling analysis on data collected from a nitrogen polluted lake (Gelda et al 1999) demonstrated that the distinct seasonal differences in NO À 2 , i.e., peak nitrite concentrations over the July to October interval (summer) compared to the rest of the year, are largely the result of differences in rate and temporal patterns of the two stages of nitrification. The abrupt nitrite peaks in September/October reflect intervals of higher nitritation than nitratation rates followed by periods of higher nitratation than nitritation rates.…”
Section: Temperaturementioning
confidence: 99%
“…As an intermediate in the two-stage nitrification process, NO2" typically has been considered to be labile (Gelda et al, 1999). However, extremely high NO2" levels prevailed in this lake's upper waters in summer and fall until the late 1990s, with concentrations often greater by a wide margin than the standard for nonsalmonids (Figure 4c) and higher than reported for any other lakes in the literature.…”
Section: B) Percent Occurrences Of Exceedances Of the Ammonia Toxicitmentioning
confidence: 65%
“…Metro inputs have caused profound water quality impacts in Onondaga Lake, as reflected in routine violations of receiving water quality standards for ammonia (Matthews et al 2000), NO 2 − (Gelda et al 1999), DO (Matthews and Effler 2006b), and clarity (Perkins and Effler 1996). Metro's P load caused the lake to be hypereutrophic, which was manifested as: (1) severe phytoplankton blooms including nuisance cyanobacteria;…”
Section: Municipal Wastementioning
confidence: 99%